Pendapatan usaha budidaya rumput laut di Desa Warampuka Kabupaten Bombana - Ulfa; Budiyanto; Annaastasia, Nurhuda; Yusuf, Sarini; Risfandi (Universitas Halu Oleo, 2024)
Warampuka Village, Bombana Regency is located in Southeast Sulawesi, where most of the people are engaged in seaweed cultivation. Types of cultivated seaweed besides Eucheuma spinosum also include Eucheuma cottonii. This study aims to determine the difference in income from the cultivation of Eucheuma spinosum and Eucheuma cottonii seaweed. This research was conducted from January to February 2023. The variables used in this study were input, output, costs, revenue and income. This research used saturated sampling method or census method with fourteen Eucheuma spinosum and Eucheuma cottonii cultivators as respondents. Data obtained through observation, interviews, documentation and literature review. The data analysis used is t test analysis. From the results of the analysis it is known that the average income of Eucheuma spinosum is IDR 28,927/10 meter while that of Eucheuma cottonii is IDR 42,517/10 meter. The results showed that the income of Eucheuma cottonii cultivation was higher than that of Eucheuma spinosum